Role of serotonin hormone, TIMP-1, and CXCL-1 indiagnosis and differentiation types of irritable bowelsyndrome - Mays Nazar; Mustafa T. ALbaldawy; Hamid K. Al-Tameemi (Journal of Health Sciences)
Introduction: Irritable bowel syndrome (IBS) is one of the most common diseases of the gastrointestinal tract. The diagnosis of IBS depends primarily on the assessment of symptoms as there are no definitive diagnostic tests. Therefore, the current study aims to fill the gap in the sequence of events mechanism to understand the pathogenesis of IBS.